Limit Theorems for Twists of L-Functions of Elliptic Curves. IV - Garbaliauskienė, Virginija; Laurinčikas, Antanas (Mathematical Modelling and Analysis, 2014)
In this paper, we prove a multidimensional limit theorem for moduli of twists of L-functions of elliptic curves. The limit measure in this theorem is defined by the characteristic transforms.